(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
Encouraging pupils to write persuasively in English is essential to their development as critical thinkers, analysts, and speakers of well-informed ideas. As persuasive reasoning and effective communication become more and more important in today’s educational environment, it is both a challenge and a need to mentor students in the subtleties of creating strong arguments. In this article the intricacies and techniques involved in instructing school children in argumentative writing are examined.